An investigation of consumers' use of 'dessert-only' food retail outlets: a mixed-methods study. Issue 9 (7th June 2021) - Randall, Tennessee; Wright, Poppy J; Wilkinson, Laura L
Abstract: Objective: To understand how consumers use 'dessert-only' retail food outlets which represent one of the UK's top ten growing retail business categories and a high-street source of energy-dense, low nutrient foods. Design: Responses to open-ended questions about dessert-only restaurant usage and closed-ended questions about demographic information including frequency of use and BMI were collected. Setting: Online questionnaire launched from the UK. Participants: Totally, 203 participants (female = 153; mean age = 33·5 years (sd = 14·2); mean BMI = 25·05 kg/m 2 (sd = 5·29)) assisted with the study. Results: Quantitative results showed that participants used dessert-only restaurants infrequently, and qualitative results showed that they regarded a visit as a treat. Many participants also described ways that they modified their eating pattern to accommodate a visit. Thematic analysis also showed that consumer visits were influenced by properties of the foods on offer, opportunities for socialisation (especially with children) as well as convenience, price and a perceived relaxation of meal-time 'rules'. Conclusions: Despite some media opinion, this type of food retail outlet is being used somewhat judiciously by consumers. A fruitful public health focus may be on the management of treats within the broader context of the diet as opposed to targeting the treat itself, this may be especially helpful for parents/caregivers taking their children out for a treat to a dessert-only restaurant.